2018
DOI: 10.1007/s00383-018-4358-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of major complications in children after laparoscopy-assisted gastrostomy and percutaneous endoscopic gastrostomy placement: a meta-analysis

Abstract: PurposeA meta-analysis was performed to compare the rates of the major complications associated with two gastrostomy tube placement techniques in a pediatric population: laparoscopy-assisted gastrostomy (LAG) and percutaneous endoscopic gastrostomy (PEG).MethodsThe PubMed electronic database was queried for comparative studies of the two insertion techniques. The Newcastle–Ottawa scale (NOS) was used for the assessment of the quality and risk of bias in the included studies. The main outcome measure was the fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 19 publications
3
39
0
Order By: Relevance
“…While some studies have evaluated the efficacy and side effects of gastrostomy from surgical or medical perspectives, still limited data are available on both aspects in the same series and on a long-term follow-up [10,11,12]. To our knowledge, no data are available about the incidence of a serious complication such as dumping syndrome, and limited data are available about the eventual need for a fundoplication procedure in a cohort of children all previously evaluated before gastrostomy positioning for gastro-esophageal reflux, as in this study.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies have evaluated the efficacy and side effects of gastrostomy from surgical or medical perspectives, still limited data are available on both aspects in the same series and on a long-term follow-up [10,11,12]. To our knowledge, no data are available about the incidence of a serious complication such as dumping syndrome, and limited data are available about the eventual need for a fundoplication procedure in a cohort of children all previously evaluated before gastrostomy positioning for gastro-esophageal reflux, as in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Another recent systematic review and meta-analysis including five retrospective studies found that while completion rates and minor complications were similar between the 550 PEG placements and 483 laparoscopic gastrostomy placements examined, significantly more bowel injuries, early tube dislodgements, and complications requiring reintervention under general anesthesia occurred after PEG placement [4]. Finally, the most recent systematic review confirmed these findings, showing that in a total of eight studies examining 1550 patients undergoing gastrostomy placement, the odds of major complications were more than three-fold higher with PEG (5.4%) compared to laparoscopic gastrostomy (1.0%) [2].…”
Section: Discussionmentioning
confidence: 81%
“…PEG is now well established as an effective method of gastrostomy placement in children and adults after its initial description by Gauderer in 1980 [1]. While some studies have shown similar safety between PEG and SG in children, several meta-analyses have recently reported a higher rate of complications with PEG [2][3][4]. These safety concerns have been most pronounced among the youngest patients [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients with severe failure to thrive and/or significant allergies, a gastrostomy tube provides stable access. However, while gastrostomy tube placement is generally associated with a low rate of complications in pediatric patients [5,6], the underlying connective tissue disorder in LDS may pose additional risks which would outweigh the benefits. We therefore undertook a retrospective cohort study of LDS patients treated at our institution to evaluate the safety and efficacy of gastrostomy tube placement in this patient population.…”
Section: Introductionmentioning
confidence: 99%